Names as a trans technology - Julia Sinclair Palm (Nordisk Tidskrift för Socioonomastik)
Children are often given a name based in some part on the sex they were assigned at birth. For trans youth, their given name does not always reflect their gender and so an aspect of their transition often includes changing their name. Drawing on interviews with trans youth in Australia, Ireland and Canada, I explore how trans youths’ naming practices offer insight into the ways that they express their desire for intelligibility and safety, while simultaneously navigating gender norms and a new sense of identity. In this paper, I engage with trans studies and critical child studies to argue that naming practices are a trans technology that trans youth use to strategically navigate gender. For some trans youth, chosen first names are described as way to be seen as one of the two societally recognized genders (man or woman), and for others, their chosen first name reflects their resistance to cisnormativity and naming practices that adhere to binary gender norms.